(untitled) (Journal of Engineering, 2026)
Previous studies have demonstrated the effectiveness of microbially stimulated calcite precipitation (MICP), produced by specific bacterial species such as Bacillus spp. , as a crack repair agent in cementitious materials. To explore its potential applications, this research investigated the effect of a bacteria-based self-healing agent on concrete containing recycled brick aggregate. The study involved isolating and culturing bacteria, identifying their species, inducing cracks, adding the bacteria, and measuring the repair efficacy of Bacillus spp. Specifically, isolated bacteria were added to samples of solid pavement composed of recycled brick aggregate, and cracks of varying sizes were created. Using 16S RNA sequencing, the characteristics of Bacillus spp. were determined. The bacteria were identified as alkaline and heat-tolerant, with amplified fragments measuring 1500 base pairs. Statistics revealed that self-healing does not always occur at the highest bacterial concentrations. Bacillus spp. produced the greatest amount of calcite at an optical density (OD600) of 1.0.X-ray diffraction (XRD) analysis indicated that Bacillus spp. can form two major components of calcium carbonate: calcite and aragonite. These results suggest that optimal bacterial concentration is necessary for effective repair, as varying calcite depositions were observed in concrete samples with different bacterial concentrations